Analysis of Risk Factors Affecting the Incidence of ARI in Toddlers in Benteng City, Selayar Islands Regency - Erwinda Alwi Rachman; Mulyadi Mulyadi; Budirman Budirman; Tsarwa Vania (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
especially in the respiratory system. Toddlers are one of the risk populations for ARI. This study aims to analyze the risk factors that influence the incidence of ARI in toddlers in Benteng Town, Selayar Islands Regency. The type of research used is analytic with a case control approach. The sampling method used was purposive sampling technique. The total number of samples was 74 samples. The results of data analysis were tested using the Chi Square test and the Logistic Regression test. The results showed that ventilation factors (p = <0.001 <0.05), occupancy density (p = 0.020 <0.05), and smoking habits of family members (p = 0.006 <0.05) were risk factors for the incidence of ARI in toddlers. The use of mosquito coils (p = 0.100 > 0.05), immunization history (p = 1.000 > 0.05), nutritional status (p = 0.563 > 0.05), and family income (p = 0.053 > 0.05) were not risk factors for ARI among children under five. The conclusion of this research is that of the seven variables studied, there are three variables that are risk factors for the incidence of ARI in toddlers, with ventilation being the most influential risk factor for the incidence of ARI in toddlers. Suggestions in this research are to maintain the cleanliness of the environment around the house and behave cleanly and healthily to prevent toddlers and families from ARI disease transmission.